Coletoras de materiais: uma nova perspectiva de renda a partir da ressignificação do material - Caetano, Marina (Universidade do Vale do Rio dos Sinos, 2015)
At the very beginning of this master’s dissertation we raise, right in the first chapter, a quick scenery in which the present study permeates, justifying socially and scientifically the importance of it based on previous studies made during graduation and specialization as well as other relevant justifications. On the second chapter we present as the general goal: to analyze the reframing that the collectors project on the collected material, matching the income generated by such activity. The research took place in Gravataí/RS, in which city the researcher has formal labor. We will also show on this item some methodological issues. The research universe consists on a qualitative research based on ethnographic approach as well as data collection made through observation and interviews with open questions to five collector women. On the third chapter we made a summary about the profession of the material collectors focusing on their importance in our society, being immerged in the social issue and also being considered as cheap work force. A brief view on the national and regional situation of the collection activity itself about the solid residual management, recycling and landfills is also presented. Also, on the third chapter we approach the consumption ease in the modernized world we live in with the facilities created so as certain social classes get purchases, goods, objects and things, considering their terminal character. The public polices also pervade this dissertation and they are divided into four categories: distributive, regulatory, redistributive and constitutive. The focus here was on the redistributive one being represented by the social policy, that is, the social assistance. On the fourth chapter we present the collector women work highlighting their individual struggle in life as well as a debate about the meaning of the material they collect. The final chapter consists of a debate on some conclusive arrangements with reflexive unfolding about the social and economic vulnerability of the Latin America. It also consists of understanding that the social policy must consider the collectors lives as the active constructions of the material reframing.
Keywords: Ressignificação; Coletoras de materiais; Política social; Reframing; Material collectors; Social policies; ACCNPQ::Ciências Humanas::Sociologia